EVALUATING THE BUILT ENVIRONMENT IN THE CONTEXT OF BARRIER FREE TOURISM, A CASE STUDY IN ISTANBUL - Yildiz, Selin; Polatoglu, Cigdem (UNIV RIJEKA, FACULTY TOURISM & HOSPITALITY MANAGEMENT, OPATIJA, 2013)
The Convention on the Rights of Persons with Disabilities by United Nations aims the elimination of discrimination against persons with disabilities and to raise their living standards. The tourism industry has also focused on Barrier-free tourism to provide better service to specific tourist groups such as; disabled people (ageing, health problems). The major issues of accessible tourism are accessible accommodation. However, before the accommodation unit, built environment itself has lots of physical barriers to deal. The aim of this paper is to emphasize the accessibility problems on the circulation patterns concerning tourism facilities and to create awareness on barrier-free tourism. The paper also deals with the confusion in disability terminology. The method of the research is depended on post- occupancy evaluation POE technique which is addressed in collaboration with architecture and tourism. The POE study consists of two phases; design of the forms (organizing access-audit forms up to Universal Design Principles) and case study. Findings show that there is a considerable amount of hotel environment and entrances which does not allow disabled to use the facilities independently.
Keywords: Barrier-free tourism; hotel design; accessibility; universal design; disability; post occupancy evaluation; Social Sciences - Other Topics